Carbon‐Encapsulated Tube‐Wire Co3O4/MnO2 Heterostructure Nanofibers as Anode Material for Sodium‐Ion Batteries. (13th August 2018) - Zhang, Wenming; Yue, Ziwei; Miao, Wenfang; Liu, Sichen; Fu, Chaochao; Li, Ling; Zhang, Zisheng; Wang, Hong
Abstract: This study presents a general approach for the synthesis of carbon‐encapsulated wire‐in‐tube Co3 O4 /MnO2 heterostructure nanofibers (Co3 O4 /MnO2 @C) via electrospinning followed by calcination. The as‐synthesized Co3 O4 /MnO2 @C is investigated as the sodium‐ion batteries anode material, which not only exhibits a high reversible capacity of 306 mAh g −1 at 100 mA g −1 over 200 cycles, but also shows a cycling stability of 126 mAh g −1 after 1000 cycles at a high current density of 800 mA g −1 . The excellent electrochemical performance can be ascribed to the contribution from carbon‐encapsulated outer‐tube Co3 O4 and inner‐wire MnO2 heterostructures, which offer a large internal space and good electrical conductivity. The present work can be helpful in providing new insights into heterostructures for sodium‐ion batteries and other applications. Abstract : Carbon‐encapsulated wire‐in‐tube heterostructure nanofibers based on electrospun and subsequent chemical bath deposition, followed by calcination, are demonstrated. This novel structure relieves the intense volume expansion and enhances the stability of the structure. The composite used as anode material demonstrates superior electrochemical performance in reversible sodium ion storage.